Os recursos sonoros da música contemporânea como ferramenta criativa no ensino musical - Audrá, Giuliana Cunha Bueno [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Knowing the shortage of artistic and pedagogical proposals involving the teaching of contemporary music in musical education institutions in Brazil I decided set out to accomplish this master thesis. It is a research-action, once worked in a non-hierarchical throughout the research process, with the aim of reshaping, restructuring, interact, engage and reassess a pedagogical practice developed in order to integrate teaching practice, theory and research. The investigation here held describes and analyses the educational activities developed by me and by the composer Sergei Kafejian in the Artistic-pedagogic Project titled Cuiabá Sonora, conducted in 2009, in the city of Cuiabá. The goal of the research was to verify whether pedagogical artistic activities developed there were able to provide participants, further development of musical artistic creativity oriented for listening, performance and creation, and if the course offered contributed to the creation of collaborative compositions entitled: ' plain, three falls and Lake ', ' the fan the bird and the maid ', ' Wall of the echo I and II ' and ' early bird at the big Theatre of erosive River Patience ' listed in the annex. It was also my aim point which sociocultural relations settled in participants groups, due to the adoption of these pedagogical practices and to what extent they were able to assist the personal and musical development of those involved. It was also my intention to verify if these educational resources could be used for other teachers in the teaching of contemporary music. The project lasted for 3 months (12 weeks) and with the participation of all students from the „ponto de cultura’ ' Project Ciranda-music and citizenship '. In it were developed some creative musical practices inspired by the educational proposals of Murray Schafer and John Paynter. Were also used musical creations procedures present in contemporary...

Sabendo da escassez de propostas artístico-pedagógicas envolvendo o ensino da música contemporânea nas instituições de ensino musical no Brasil é que me propus a realizar esta dissertação de mestrado. Trata-se de uma pesquisa-ação, uma vez que atuei de forma não hierárquica em todo o processo de investigação, com o intuito de remodelar, reestruturar, interagir, dialogar e reavaliar uma prática pedagógica desenvolvida, de forma a integrar prática docente, teoria e pesquisa. A investigação aqui realizada descreve e analisa as atividades pedagógicas desenvolvidas por mim e pelo compositor Sérgio Kafejian no Projeto Artístico-Pedagógico intitulado Cuiabá Sonora, realizado em 2009, na cidade de Cuiabá. O objetivo da pesquisa foi verificar se as atividades artístico pedagógicas ali desenvolvidas foram capazes de propiciar aos participantes, maior desenvolvimento da criatividade artístico-musical voltada para escuta, performance e criação e se realmente o curso ofertado contribuiu para a criação das composições colaborativas intituladas: „Planície, três quedas e lago‟, „O ventilador o pássaro e a camareira‟, „Paredão do eco I e II‟ e „Pássaro da manhã no grande teatro erosivo do Rio Paciência‟, constantes no anexo. Também foi meu intuito apontar quais relações socioculturais se estabeleceram nos grupos participantes, em razão da adoção destas práticas pedagógicas e em que medida elas puderam auxiliar o desenvolvimento musical e pessoal dos envolvidos. Foi ainda minha intenção verificar se esses recursos pedagógicos poderiam ser utilizados por outros docentes no ensino da música contemporânea. O projeto teve a duração de 3 meses (12 semanas) e contou com a participação de todos os alunos do Ponto de Cultura „Projeto Ciranda-Música e Cidadania‟. Nele foram desenvolvidas algumas práticas musicais criativas inspiradas nas propostas de ensino....
Keywords: Musica - Instrução e estudo; Música - Séc. XXI; Criação (Literária, artística, etc.); Music - Instruction and study